Two-Component Signal Transduction Systems of Pathogenic Bacteria As Targets for Antimicrobial Therapy: An Overview - Tiwari, Sandeep; Jamal, Syed B.; Hassan, Syed S.; Carvalho, Paulo V. S. D.; Almeida, Sintia; Barh, Debmalya; Ghosh, Preetam; Silva, Artur; Castro, Thiago L. P.; Azevedo, Vasco (Frontiers in Microbiology, 2017)
The bacterial communities in a wide range of environmental niches sense and respond to numerous external stimuli for their survival. Primarily, a source they require to follow up this communication is the two-component signal transduction system (TCS), which typically comprises a sensor Histidine kinase for receiving external input signals and a response regulator that conveys a proper change in the bacterial cell physiology. For numerous reasons, TCSs have ascended as convincing targets for antibacterial drug design. Several studies have shown that TCSs are essential for the coordinated expression of virulence factors and, in some cases, for bacterial viability and growth. It has also been reported that the expression of antibiotic resistance determinants may be regulated by some TCSs. In addition, as a mode of signal transduction, phosphorylation of histidine in bacteria differs from normal serine/threonine and tyrosine phosphorylation in higher eukaryotes. Several studies have shown the molecular mechanisms by which TCSs regulate virulence and antibiotic resistance in pathogenic bacteria. In this review, we list some of the characteristics of the bacterial TCSs and their involvement in virulence and antibiotic resistance. Furthermore, this review lists and discusses inhibitors that have been reported to target TCSs in pathogenic bacteria.